ANALISIS KECENDERUNGAN PENELITIAN SKRIPSI MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA UNIVERSITAS MUHAMMADIYAH SUKABUMI TAHUN AKADEMIK 2014-2015 - Nur'aini Muhassanah; Aritsya Imswatama (Universitas Muhammadiyah Pringsewu, 2016)
The purpose of this research describe the distribution and trends of the undergraduate thesis that conducted by the Mathematics Education Department students in terms of the research type, focus of the research, research materials, and research subject, and also describe the difficulties experienced by the students. This research is a qualitative case study. The subjects of the research are 8 th semester of Mathematics Education Department students in the academic year 2014-2015. The data collecting technique used questionnaire and interview methods. The data validity used triangulation method, coordinating between questionnaire and interview data. Results of this research are: (1) the type of student research is quantitative; (2) the focus of the research is learning model and problem solving; (3) the research material is Geometri; and (4) the research subject is junior high school students. In addition, the results obtained the student difficulties in arrange the undergraduate thesis and also the solutions are: (1) they can't organize their time, the solution make a good planning, (2) the difficulty in finding, determine the problem, and also determine the undergraduate thesis title, the solution make an undergraduate thesis map activities; (3) the difficulty of processing and data analysis and also the laziness, the solution is motivate yourself; (4) The difficulty to meet the lecturers, the solution is discuss with friends, lecturers, and also family; and (5) the difficulty during made the instrument, the solution is looking for and reading references. Keywords: trends of the undergraduate thesis , distribution of the undergraduate thesis